OP X – 5 Long-term exposure to air pollution and biomarkers of inflammation and insulin resistance in a longitudinal setting. (18th March 2018) - Mwiberi, Sarah; Wolf, Kathrin; Rückerl, Regina; Breitner, Susanne; Huth, Cornelia; Koenig, Wolfgang; Rathmann, Wolfgang; Herder, Christian; Roden, Michael; Cyrys, Josef; Peters, Annette; Schneider, Alexandra E
Abstract : Background/aim: Exposure to outdoor air pollution has been associated with systemic inflammation but results have been inconsistent. Evidence for deleterious effects on glucose metabolism and insulin resistance is still limited. We investigated the association of long-term air pollution exposure on biomarkers of systemic inflammation, glycaemia, and insulin resistance measured up to three times. Methods: We used baseline survey (1999–2001), first follow-up (2006–2008) and second follow-up (2013–2014) from the KORA study in Augsburg, Southern Germany. At each examination, we measured plasma high-sensitivity C-reactive protein (hsCRP), glycosylated haemoglobin (HbA1c) and homeostatic model assessment of insulin resistance (HOMA-IR) calculated from fasting glucose and insulin. We estimated residential long-term exposure to ultrafine particles (UFP), different size fractions of particulate matter, soot, nitrogen oxides and ozone by land use regression. Associations between annual pollutants and biomarkers were modelled using generalised estimating equations adjusting for socio-demographic, lifestyle and clinical covariates. Potential effect-modifiers were examined by use of interaction terms. Results: We included 9590 observations from 4255 participants aged 25 to 75 years at baseline in the analyses. Air pollutant concentrations at the participants' residences were well below the EU guidelines for regulated pollutants. Except for ozone, all pollutants were positively associated with at least one of the biomarkers. For UFP, the highest effect was seen for hsCRP with an increase of 3% (95% CI: 0.4 to 5.6) per 1900 particles/cm 3 increase. Particulate matter between 2.5 and 10 µg/m³, soot and nitrogen dioxides were significantly associated with HbA1c and HOMA-IR. For the latter, effect estimates tended to be higher for males and elderly participants while this was not the case for the other two biomarkers. Conclusion: The findings of this longitudinal study add to a scarce body of literature on cardiometabolic health effects in association with chronic exposure to air pollution and help to fill the existing research gap, especially with regard to the effects of ultrafine particles.